2012
DOI: 10.1590/s0100-204x2012000900011
|View full text |Cite
|
Sign up to set email alerts
|

Correlação de variáveis espectrais e estoque de carbono da biomassa aérea de sistemas agroflorestais

Abstract: Resumo -O objetivo deste trabalho foi avaliar a correlação entre variáveis espectrais e o estoque de carbono da biomassa aérea de sistemas agroflorestais da região de Tomé-Açu, PA. Foram testados 24 índices de vegetação de três grupos (razão simples, diferença normalizada e complexos), gerados a partir de imagens do sensor TM/ Landsat-5, adquiridas em 2008. As variáveis obtidas foram correlacionadas, por meio de regressão linear simples, ao estoque de carbono de quatro classes de sistemas agroflorestais, de di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
(17 reference statements)
0
9
0
5
Order By: Relevance
“…In the case of healthy vegetation, the presence of pigments in the leaves such as chlorophyll, carotenes and xanthophylls are responsible for a greater absorption of electromagnetic radiation in the visible region, mainly in the red region (Ponzoni et al, 2012). Other studies found similar results with high correlations between basal area and TM3, TM4, TM5 and TM7 bands (Berra et al, 2012;Bolfe et al, 2012;Almeida et al, 2014).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…In the case of healthy vegetation, the presence of pigments in the leaves such as chlorophyll, carotenes and xanthophylls are responsible for a greater absorption of electromagnetic radiation in the visible region, mainly in the red region (Ponzoni et al, 2012). Other studies found similar results with high correlations between basal area and TM3, TM4, TM5 and TM7 bands (Berra et al, 2012;Bolfe et al, 2012;Almeida et al, 2014).…”
Section: Resultsmentioning
confidence: 68%
“…According to Ponzoni et al (2015) the reflectance of eucalyptus stands older than 6 years is influenced by Where: ND= Normalized Difference; NDVI= Normalized Difference Vegetation Index; G = basal area (m 2 .ha -1 ); HD = dominant height (m); V = volume (m 3 .ha -1 ); ns = not significant at 5% and *significant at 5%. green leaf loss and the greater participation of litter (including dry branches deposited on the ground), therefore explaining the highest correlations with the SAVI and MSAVI indices at age 7 years, since these indices are constructed to attenuate soil influence on vegetation reflectance (Bolfe et al, 2012).…”
Section: /8mentioning
confidence: 99%
“…As demais variáveis (SR, NDVI, EVI 2 e Savi), todas provenientes de sensoriamento remoto, apresentaram correlações que variaram de fracas a moderadas (Tabela 1). Bolfe et al (2012) Almeida et al (2014) e Ferraz et al (2014. A superioridade destas estatísticas pode estar relacionada tanto à alta intensidade amostral (18% da área foi amostrada) quanto às características da resolução espacial e espectral do sensor LISS-III e às características da vegetação estudada.…”
Section: Resultsunclassified
“…When this occurs, NDVI becomes insensitive to biomass changes, which may have reflexes on productivity (POVH et al, 2008). For this reason, the simple index ratio (RVI, RNIR/RR) and inverse ratio (IRVI, RR/RNIR) have also been studied to predict the biomass in areas with higher intensity of vegetation, since these indexes are less susceptible to saturation (HATFIELD & PRUEGER, 2010;LI et al, 2010;BOLFE et al, 2012).…”
Section: Introductionmentioning
confidence: 99%